Studi Kasus: Optimasi Sistem Perpipaan Dengan Lengkung Ekspansi Tipe V - Danur Riswanto; Ryan Fitrian Pahlevi; Faiz Nurul Qolbi; Eric Topattinaya; Muhammad Shandy Putra Prasetyo (CV. IRA PUBLISHING, 2025)
Industrial piping systems that transport high-temperature fluids are susceptible to thermal expansion, which can cause excessive axial stress and structural failure risks. This study aims to optimize the V-Type expansion bend design to enhance material efficiency while ensuring stress levels remain within the allowable limits set by ASME B31.3. Simulations were conducted using CAESAR II software version 2014, incorporating real project data on pipe geometry, materials, and operating conditions. The results indicate that the V-Type expansion bend requires the shortest total pipe length-5452 mm-while producing a thermal stress ratio of 30%, outperforming the U-Type bends by Thermacor (6069 mm, 20.8%) and Bahaa (10000 mm, 15.8%). The V-type configuration also results in lower nozzle loads and moments, making it a safer and more cost-effective solution for field implementation.